Research trends in the use of secondary batteries for energy storage - García-Pineda, Vanessa; Valencia-Arias, Alejandro; Zapata Ochoa, Edison Andrés; Sánchez-Santos, Gustavo; Gastiaburú-Morales, Silvia Yvone; Palacios-Moya, Lucia (Frontiers in Environmental Science, 2024)
This study addresses the use of secondary batteries for energy storage, which is essential for a sustainable energy matrix. However, despite its importance, there are still important gaps in the scientific literature. Therefore, the objective is to examine the research trends on the use of secondary batteries for energy storage and to assess their development and direction. A bibliometric analysis is used, followaing the PRISMA-2020 guidelines for the analysis of secondary sources. 98 studies were identified and analyzed in the bibliometric evaluation category. Although this is a review of different research documents and different types of batteries are addressed, the study focuses mainly on the identification of the different existing trends in the use of second-use batteries for energy storage. The study's findings show a significant increase in interest, particularly in 2023, 2022, and 2021. Key researchers such as Zakeri and Kulcinski, as well as journals like Energy Conversion and Management, have made significant contributions. The significance of the topic is highlighted by the annual production of articles. The leading research in this field comes from the US and China, with a shift in focus towards specific areas such as thermal assessment and storage. Thematic clusters include life cycle analysis, thermal storage, and lithium-ion batteries. Emerging terms such as 'smart grid' and 'exergy' indicate a growing interest. Understanding trends in battery research is crucial for developing sustainable energy solutions and addressing global energy challenges.